Short-Term Motor Outcomes in Parkinson's Disease after Subthalamic Nucleus Deep Brain Stimulation Combined with Post-Operative Rehabilitation: A Pre-Post Comparison Study. (12th August 2022) - Sato, Kazunori; Hokari, Yoshihide; Kitahara, Eriko; Izawa, Nana; Hatori, Kozo; Honaga, Kaoru; Oyama, Genko; Hatano, Taku; Iwamuro, Hirokazu; Umemura, Atsushi; Shimo, Yasushi; Hattori, Nobutaka; et al.
Abstract : Background . The effects of subthalamic nuclear deep brain stimulation therapy (STN-DBS) and combined postoperative rehabilitation for patients with Parkinson's disease with postural instability have yet to be well reported. This study investigated the effects of short-term postoperative rehabilitation with STN-DBS on physical function in patients with Parkinson's disease. Methods . Patients diagnosed with Parkinson's disease who were admitted to our hospital for STN-DBS surgery were included in this study. Data were prospectively collected and retrospectively analyzed. Postoperative rehabilitation consisted of muscle-strengthening exercises, stretching, and balance exercises for 40–60 minutes per day for approximately 14 days. The Mini-Balance Evaluation Systems Test (Mini-BESTest), Timed Up and Go test (TUG) seconds and steps, Trunk Impairment Scale (TIS), seconds for 10 times toe-tapping, lower limb extension torque using StrengthErgo240, and center of pressure sway in the quiet standing posture were evaluated preoperatively, postoperatively, and at discharge. Mini-BESTest changes were also evaluated in the two groups classified by the presence or absence of postural instability. One-way and two-way repeated measures analyses of variance were performed for each of the three periods of change, and paired t -tests with the Bonferroni method were performed as multiple comparison tests. A stepwise multiple regression model was used to identify factors associated with balance improvement. Results . A total of 60 patients with Parkinson's disease were included, and there were significant increases in Mini-BESTest, TIS, StrengthErgo240, and postural sway during closed-eye standing compared to pre- and postoperative conditions at discharge (p < 0.05 ), and they decreased significantly compared to the postoperative period (p < 0.05 ). On stepwise multiple regression analysis, decreased steps of TUG and improvement of TIS scores were related to improvement of the Mini-BESTest (p < 0.05 ). In addition, Mini-BESTest scores in both groups with and without postural instability were significantly increased at discharge compared to preoperative and postoperative conditions (p < 0.01 ). Conclusion . Postoperative rehabilitation combined with STN-DBS may provide short-term improvements in physical function compared with the preoperative medicated status. The improvements in gait step length and trunk function may be important factors for obtaining improvement of postoperative postural stability.